2014
DOI: 10.1177/0194599814556250
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Incidence of Postoperative Hypocalcemia following Total Thyroidectomy vs Completion Thyroidectomy

Abstract: The risk of transient of hypocalcemia in patients undergoing CT is significantly lower than the rate of hypocalcemia in patients undergoing TT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 19 publications
1
47
2
1
Order By: Relevance
“…Factors contributing to this may be more chances of fibrosis & compromised vascularity to parathyroid glands in a previously operated neck as well as unknown functional status of the parathyroid glands on the previously operated side. But this is in contrary to the findings of González-Botas and Piedrahita 42 and Merchavy et al, 43 who reported that postoperative hypocalcaemia was less common in patients with completion thyroidectomy than in patients who underwent total thyroidectomy. However, other authors like Godlewska P, et al reported incidence of hypoparathyroidism to be 15.74% following radical thyroid surgery versus 23.43% after completion thyroidectomy, supporting the data obtained in the current study.…”
Section: Discussioncontrasting
confidence: 76%
“…Factors contributing to this may be more chances of fibrosis & compromised vascularity to parathyroid glands in a previously operated neck as well as unknown functional status of the parathyroid glands on the previously operated side. But this is in contrary to the findings of González-Botas and Piedrahita 42 and Merchavy et al, 43 who reported that postoperative hypocalcaemia was less common in patients with completion thyroidectomy than in patients who underwent total thyroidectomy. However, other authors like Godlewska P, et al reported incidence of hypoparathyroidism to be 15.74% following radical thyroid surgery versus 23.43% after completion thyroidectomy, supporting the data obtained in the current study.…”
Section: Discussioncontrasting
confidence: 76%
“…In our meta-analysis, only 2 of the included studies [5,9] mentioned central lymph node dissection as part of the surgical procedure. One of these 2 studies [9] did not consider the presence of lymph nodes in the surgical specimens, and the other one [5] found a similar incidence of hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…In our meta-analysis, only 2 of the included studies [5,9] mentioned central lymph node dissection as part of the surgical procedure. One of these 2 studies [9] did not consider the presence of lymph nodes in the surgical specimens, and the other one [5] found a similar incidence of hypocalcemia. Although our study cohort was short of these data, some authors indicated that central lymph node dissection was not a risk factor for postoperative hypocalcemia [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the Freire et al pediatric thyroidectomy prospective longitudinal cohort study demonstrated similar transient hypocalcemia rates of 47% and symptomatic hypocalcemia rates of 15% [10]. In contrast, adult literature suggests transient hypocalcemia rates of 1.5-52% of cases [12][13][14]. This variability may be secondary to differences in defining hypocalcemia.…”
Section: Accepted Manuscript #12mentioning
confidence: 91%
“…One retrospective study on adults suggests transient hypocalcemia occurred in 1.5% of patients that underwent a completion thyroidectomy and 12.5% of patients that underwent a total thyroidectomy. There may be a significantly lower risk for hypocalcemia following a completion thyroidectomy compared to a total thyroidectomy [12]. Future studies should be performed in a larger pediatric cohort to determine whether patients undergoing completion thyroidectomy are equally at risk for developing postoperative hypocalcemia as those undergoing total thyroidectomy.…”
Section: Accepted Manuscript #12mentioning
confidence: 99%